OBSERVATIONS ON THE ROMAN OCCUPATION OF THE VALLEY OF THE MIRA - Correia, Virgílio Hipólito (Conimbriga, 2015)
An integrated approach to available data on the Roman occupation of the Mira River Valley (Alentejo, Portugal) is presented; the scarcity thereof is interpreted as a situation arising from the concrete historical path taken, rather than the product of insufficient research. In this context the situation of the Roman town of Arandis is discussed, and its location proposed at the so-called Castro da Cola (Ourique), on the basis of archaeological arguments and the linguistics of the place-name. The originality of the Roman occupation of the area and the historical roots of the situation are discussed from a theoretical and anthropological point of view, using concepts from landscape archeology.